TRUMP TARIFF ON INDONESIA STOCK EXCHANGE. DOES THE MARKET RECOVER ONE MONTH AFTER THE ANNOUNCEMENT? - Kiky, Andreas (ULTIMA Management, 2025)
Abstract - This study examines the Indonesian stock market's reaction to the U.S. tariff announcement on April 1, 2025. The Indonesian Stock Market tends to overreact to the Trump Announcement. This paper presents the latest empirical findings on the effect of the Trump Tariff announcement, made immediately after the market reopened following a long holiday and a month after the event. Employing an event study methodology, the research analyses abnormal returns of 782 listed firms using the Capital Asset Pricing Model (CAPM) to estimate expected returns. The analysis focuses on two critical points: April 8th 2025, when the market reopened after the announcement, and April 30th, the end of the post-event window. The findings reveal a significant negative abnormal return immediately after the market reopened, followed by a strong positive abnormal return at the end of the month. A paired-sample test confirms a statistically significant difference in abnormal returns between these two periods. Cross-sectional analysis across beta tertiles shows that systematic risk levels influenced investor reactions, with low-beta stocks experiencing the most pronounced reversal. These results highlight the sensitivity of emerging markets to global policy shifts and underscore the importance of risk exposure in shaping investor behaviour. Keywords: Event Studies; Tariff Effect; Abnormal Return; Efficient Market Hypothesis; Policy Spilover